A Literature Review on the Effectiveness of LKPD based Local Wisdom–Integrated STEAM Approach in Improving Students’ Critical Thinking Skills - Dhea Irani; Rahmatta Thoriq Lintangesukmanjaya; Neisya Azaria Adinda Putri (Journal of Current Studies in SDGs, 2025)
Objective: To improve students' critical thinking skills, this study aims to present findings from a literature review on the effectiveness of LKPD, a STEAM-based approach grounded in local wisdom. Method: Literature review is a research methodology used and involves searching several scientific works from trusted sites such as Google Scholar, ERIC, Scopus, and CABI, then analyzing them by creating a literature review Matrix, which later describes the results of the analysis obtained from 31 articles used as references.  Results: In this study, the conclusion was that worksheets for learners (LKPD) based on local wisdom, with a STEAM approach, were valid, practical, and effective. The integration of LKPD, local wisdom, and STEAM supports meaningful and empowering learning and enhances critical thinking skills to address challenges in the 21st century.  Novelty:   The findings indicate that Local Wisdom–based STEAM learning can be an innovative and contextual instructional strategy to foster higher-order thinking skills. This approach supports student-centered learning by encouraging creativity, engagement, and deeper conceptual understanding.